The preparation of intrinsic DOPO-Cinnamic flame-retardant cellulose and its application for lithium-ion battery separator - Jianxin Liu; Dujian Qin; Ken Chen; Bo Wang; Hongli Bian; Ziqiang Shao (Materials Research Express, 2021)
A renewable and superior intrinsic thermal-resistant cellulose-based nonwoven was explored as lithium-ion battery separator via phase separation mechanism. Herein, we sparked a robust strategy for improving the flammability of cellulose, namely DOPO- Cinnamoyl Cellulose (DCC) with intrinsic flame retardant was obtained via the incorporation of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and Cinnamoyl Chloride attached on the backbone of cellulose. It demonstrates that the heat release rate and total heat release significantly reduced. Meanwhile the membrane displayed excellent self-extinction. Additionally, after the DCC membrane assembled into lithium battery, under the optimum formulation situation, the electrochemical properties established that the LIBs showed superior electrochemical performance compared with PP separator. The interface impedance of DCC separator was less than 300 Ω, which was much smaller than that of commercial separator of 410 Ω. After 50 cycles, the battery with DCC-0.11 separator retained 84.2% of its initial discharge capacity, which was higher than the commercial polypropylene separator with the numeric of 79.1%. In sum, this novel, environmental friendly and intrinsic DOPO-Cinnamic flame-retardant cellulose based separator can be considered as an expectant candidate for lithium ion battery separator with high performance.